Analisis Peramalan Permintaan Golang-Galing dalam Memaksimalkan Manajemen Rantai Pasok Menggunakan Metode Weighted Moving Average - Ajeng Nurdina; Dyah Aryani; Ella Venita; Sarah Astiti (JURIKOM (Jurnal Riset Komputer), 2022)
Forecasting the demand for golang-galing products in the Small and Medium Enterprises (SMEs) industry “Pak Liman” in Kaliori Village, Banyumas District, Banyumas Regency is planning support in production control so as to maximize supply chain management of golang-galing products. Forecasting market demand is very necessary in order to predict market opportunities for future demand for a product. Demand forecasting aims to prevent the risk of sales prediction errors that cause waste such as sales predictions that are too large which can lead to swelling in production costs and vice versa if sales predictions are too small it will result in out of stock out, so consumers need to wait a long time for sales. get the desired product. Based on these problems, an analysis of demand forecasting for golang-galing products is carried out which aims to reduce waste and maximize value for all components in the supply chain. This study uses time series analysis with the moving average method to forecast the demand for golang-galing products for the next five months. The results of the study obtained forecasting in April, May, June, July, August, September, October, November, December 2022 in sequence, namely 3,254.6; 3,254; 3,256.6; 3,254, 6; 3,254.2; 3,253.9; 2,987.3; 3,162,9; 3,156.4. From the calculation of the Mean Absolute Error (MAE) and Mean Square Error (MSE) that has been carried out, it is obtained that the calculation for MAE is 3.44 and MSE is 20.144.